Buzz Aldrin pilot of the first moon landing - Casil, Amy Sterling (New York : Rosen Pub. Group, 2004)
Profiles the astronaut who served as the lunar module pilot for the Apollo 11 mission and became the second man to set foot on the moon.
A lone ranger -- Finding his way -- From combat pilot to astronaut -- Astronaut in training -- Walking in space -- Men on the Moon -- Stargazing.
8 - 12 years
Keywords: Aldrin, Buzz -- Juvenile literature; Astronauts -- United States -- Biography; Astronauts